2014
DOI: 10.1111/jopr.12190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermocycling on the Shear Bond Strength of Different Resins Bonded to Thermoplastic Foil Applied in Occlusal Splint Therapy

Abstract: The shear bond strength between the self-cured resin and the thermoplastic foil was higher and more resistant to aging than the shear bond strength between the light-cured resin and the thermoplastic foil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Similarly, studies on thermoplastic foils, in particular those with a build-up made of an LC resin, are scarce. 14 A study by Patzelt et al revealed that a digital workflow was more time-efficient, and the fit of the digitally-fabricated splints was better than that of the conventionally-fabricated ones. The wear of the 2 different materials showed comparable results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, studies on thermoplastic foils, in particular those with a build-up made of an LC resin, are scarce. 14 A study by Patzelt et al revealed that a digital workflow was more time-efficient, and the fit of the digitally-fabricated splints was better than that of the conventionally-fabricated ones. The wear of the 2 different materials showed comparable results.…”
Section: Discussionmentioning
confidence: 99%
“…The technology is used to produce prosthetic restorations, dental models, implants, surgical guides, custom trays, orthodontic appliances, and occlusal splints. [13][14][15][16][17] Furthermore, it provides a simple means of manufacturing complex, customdesigned objects, reducing material waste and working time. 18,19 Despite its many advantages, there are several limitations to 3D printing that require comprehensive research into the materials and techniques used in the fabrication of oral appliances.…”
Section: Introductionmentioning
confidence: 99%
“…Some new, more resistant materials are being searched for; however, most of the attention of the producers focuses on the composite blocks used for teeth restoration [25]. Another interesting study [26] showed the shear bond strength of materials used for the fabrication of occlusal splints, which shows that not only 3D-printed materials are influenced by the artificial aging procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1,000 cycles were performed. Then the specimens were tested for SBS 34) . For shear bond testing, a chisel was connected to a Universal Testing Machine (AG-IS 500N, SHIMADZU, Kyoto, Japan).…”
Section: Enamel Shear Bond Strength (Sbs)mentioning
confidence: 99%